Biological control of Trichoderma spp.: Mechanisms of action against phytopathogens, insect pests, and its multifaceted roles in agro-ecosystems - Praveen Thangaraj; Akshaya Subbiah Balamurali; Nivedha Muthusamy (Environment Conservation Journal)
Trichoderma, a prominent genus of fungi within the Hypocreales order, is widely used in agriculture due to its effectiveness in managing phytopathogens and insect pests. sect pests. Furthermore, Trichoderma species improve soil fertility and structure, playing a vital role in overall ecosystem health. The capacity of certain species to control specific insect pests makes them an important part of integrated pest management approaches. This review provides a comprehensive overview of Trichoderma spp.'s biological potential and its mechanisms for controlling phytopathogens and insect pests. Known for their mycoparasitic, biocontrol, and plant growth-promoting properties, Trichoderma species can suppress a broad spectrum of insect pests through several mechanisms. This review explores the specific strategies Trichoderma employs in pest management, including the production of secondary metabolites, competition for resources, and disruption of pest life cycles. It also looks at how well Trichoderma-based biocontrol agents work with other biological control methods. This is done to highlight the potential for integrated pest management (IPM) strategies that better get rid of pests while having less of an effect on the environment. Beyond their direct effects on insect pests, Trichoderma species are also beneficial for plant health and growth. This review addresses how Trichoderma improves plant resilience, potentially lowering crop vulnerability to insect infestations. In addition, the use of biocontrol agents underscores their promise in sustainable agriculture by minimizing the need for chemical pesticides and supporting eco-friendly farming methods to develop new and innovative solutions.